Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1063/1.4935487
|View full text |Cite
|
Sign up to set email alerts
|

Folding and insertion thermodynamics of the transmembrane WALP peptide

Abstract: A refined polarizable water model for the coarse-grained MARTINI force field with long-range electrostatic interactions The Journal of Chemical Physics 146, 054501 (2017) The anchor of most integral membrane proteins consists of one or several helices spanning the lipid bilayer. The WALP peptide, GWW(LA) n (L)WWA, is a common model helix to study the fundamentals of protein insertion and folding, as well as helix-helix association in the membrane. Its structural properties have been illuminated in a large numb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 88 publications
(162 reference statements)
5
65
0
2
Order By: Relevance
“…In comparison to the AA PMFs of WALP16 insertion, it appears PACE is overstabilizing the interfacial state. This same problem was observed in pure MARTINI simulations, although there the interfacial state of WALP16 was globally stable and the barrier separating TM and interfacial states was considerably larger than what we compute for PACE . In the same paper by Bereau et al, they compute an atomistic insertion PMF, which shows a similar barrier between interfacial and TM configurations as we compute in PACE, but the TM state free energy is lower than the interfacial state by ∼7 kcal/mol.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In comparison to the AA PMFs of WALP16 insertion, it appears PACE is overstabilizing the interfacial state. This same problem was observed in pure MARTINI simulations, although there the interfacial state of WALP16 was globally stable and the barrier separating TM and interfacial states was considerably larger than what we compute for PACE . In the same paper by Bereau et al, they compute an atomistic insertion PMF, which shows a similar barrier between interfacial and TM configurations as we compute in PACE, but the TM state free energy is lower than the interfacial state by ∼7 kcal/mol.…”
Section: Resultssupporting
confidence: 82%
“…Atomistic simulations are suited to examine this problem, but differing results have been reported. Unbiased simulations have shown unfolding to occur in solution, while metadynamics simulations have shown both folded and unfolded conformations are thermally accessible and the folded state is the free energy minimum . There is a possibility that PACE is overstabilizing the helical content in the aqueous phase, but it does show that the membrane environment can influence the peptide structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Komplexitätvieler biomolekularer Systeme schränkt die Mçglichkeiten von atomaren Simulationen -i nd enen alle Atome explizit dargestellt sind -s elbst mit heutigen Rechenmethoden und Computern stark ein. [106] Das Modell hat ebenfalls gezeigt, dass es in der Lage ist, einfache Sequenzen in der Membran, wie z. Coarse-grained, also systematisch vergrçberte Modelle vereinigen mehrere Atome zu einem grçßeren Partikel oder einer grçßeren Kugel und sorgen dadurch füre ine erhebliche Beschleunigung der Berechnungen.…”
Section: Multiskalensimulationen Der Proteinkonformation Und -Faltungunclassified
“…45 They found that only the Martini force field exhibits a pronounced secondary minimum for an interfacial adsorbed state. 45 They found that only the Martini force field exhibits a pronounced secondary minimum for an interfacial adsorbed state.…”
Section: Potential Of Mean Forcementioning
confidence: 99%